Analisis Spasial Pengaruh Infrastruktur Sosial Dan Infrastruktur Ekonomi Terhadap Kemiskinan Pulau Jawa 2021 - Gabriela, Patrisia; Utomo, Agung Priyo (Politeknik Statistika STIS, 2023)
Java Island is the center of Indonesia's development with poverty problems still a major concern. Compared with other islands, Java Island experienced the highest growth in poverty rate during the COVID-19 phenomenon in 2021. Based on regional characteristics, infrastructure is one of the determinants of poverty. Even today, infrastructure development is one of the five main directions of the government. When considering infrastructure development, Java Island is an island with adequate infrastructure compared to other islands. However, the adequacy of Java Island's infrastructure is not in line with the conditions of the poverty rate in 2021. The pattern of poverty rate distribution among districts/cities on Java Island shows a clustering trend. It is necessary to further analyze the effect of social and economic infrastructure on the poverty rate in Java in 2021 by considering spatial effects. The data used comes from the Central Bureau of Statistics. The analysis method uses the spatial error model (SEM). The results showed a positive spatial autocorrelation in the poverty rate. The results of this study indicate that social (health facilities) and economic infrastructure (access to electric lighting sources and access to adequate sanitation) have a significant effect on the reduction.